Determinants of High-Risk Human Papillomavirus Seroprevalence and DNA Prevalence in Mid-Adult Women. Issue 3 (March 2016) - Sadate-Ngatchou, Patricia; Carter, Joseph J.; Hawes, Stephen E.; Feng, Qinghua; Lasof, Taylor; Stern, Joshua E.; Fu, Tsung-chieh (Jane); Galloway, Denise A.; Koutsky, Laura A.; Winer, Rachel L.
Abstract : Background: The epidemiology of high-risk human papillomavirus (hrHPV) infections in mid-adult women is not well understood. Methods: We conducted a cross-sectional analysis of 379 women 30 to 50 years of age. Vaginal samples were tested for type-specific HPV DNA by polymerase chain reaction. Sera were tested for type-specific HPV antibodies by Luminex-based assay. Assays included 13 hrHPV types (16/18/31/33/35/39/45/51/52/56/58/59/68). Self-reported health and sexual history were ascertained. Risk factors for seropositivity and DNA positivity to hrHPV were assessed in separate Poisson regression models. Results: The mean (SD) age of participants was 38.7 (6.1) years, and the median lifetime number of male sex partners was 7. Approximately two-thirds (68.1%) were seropositive for any hrHPV, 15.0% were DNA positive, and 70.7% were seropositive or DNA positive. In multivariate analyses, women who were married/living with a partner were less likely to be seropositive than single/separated women (adjusted prevalence ratio [aPR], 0.86; 95% confidence interval [CI], 0.75–0.98). Compared with never hormonal contraceptive users, current (aPR, 1.53; 95% CI, 1.01–2.29) or former (aPR, 1.64; 95% CI, 1.10–2.45) users were more likely to be seropositive. Women with a lifetime number of sex partners of 12 or more were more likely to be seropositive compared with those with 0 to 4 partners (aPR, 1.29; 95% CI, 1.06–1.56). Similar associations were seen with DNA positivity. In addition, there was a positive association between current smoking and hrHPV DNA (aPR vs. never smokers, 2.51; 95% CI, 1.40–4.49). Conclusions: Seventy-one percent of mid-adult women had evidence of current or prior hrHPV infection. Measures of probable increased exposure to HPV infection were associated with both seropositivity and DNA positivity to hrHPV, whereas current smoking was positively associated with hrHPV DNA only. Abstract : Seventy-one percent of mid-adult women showed evidence of current or prior infection with high-risk human papillomavirus. Measures of probable increased exposure were associated with both seropositivity and DNA positivity to high-risk human papillomavirus.